Challenges to manage pandemic of coronavirus disease (COVID-19) in Iran with a special situation: a qualitative multi-method study - Hamidreza Khankeh; Mehrdad Farrokhi; Juliet Roudini; Negar Pourvakhshoori; Shokoufeh Ahmadi; Masoumeh Abbasabadi-Arab; Nader Majidi Bajerge; Babak Farzinnia; Pirhossain Kolivand; Vahid Delshad; Mohammad Saeed Khanjani; Sadegh Ahmadi-Mazhin; et al. (BMC, 2021)
Abstract Background With the unprecedented expansion of COVID-19 in the world since December 2019, Iran's health system, like other countries, faced various challenges in managing the disease, which led to numerous experiences and lessons learned. This study was conducted to identify these challenges regarding unique political, economic, and cultural issues, which could help other countries with similar situations. Methods The present study was performed using a qualitative multi-method approach with a content analysis method. The data were collected through in-depth and semi-structured interviews and focused group discussions with 60 key persons who were selected purposefully, including policymakers, health care workers, and affected people by the disease, and the review of all available national reports between February 21, 2020, and March 22, 2021. The data collection and analysis were done simultaneously. Results Identified critical challenges for the management of COVID-19 in the health system were limited evidence and scientific controversies, poor social prevention and social inequalities, burnout and sustained workload among healthcare workers, improper management of resources and equipment, the lack of a guideline for contact tracing, and patient flow management, and mental health problems in the community. Conclusions According to our results, measures should be taken to conduct a continuous comprehensive risk assessment and develop a national response plan with an emphasis on precise contact tracing, active screening, patient flow, paying attention to the psychological and social dimensions of the disease, and also transparency of social inequalities in the face of risk factors of the COVID-19. Also, the social protection programs should become a vital tool for policymakers and supporting the vulnerable groups using the capacity of the community and international cooperation to develop a vaccine, which is difficult to procure due to the sanctions.